Multi-keywords carrier-free text steganography method based on Chinese Pinyin. (6th March 2020) - Liu, Yuling; Wu, Jiao; Xin, Guojiang
By combining big data with the characteristics of steganography, carrier-free steganography was proposed to resist all the steganalysis attacks. A novel method named multi-keywords carrier-free text steganography method based on Chinese Pinyin is introduced in this paper. In the proposed method, the hidden tags are selected from the Pinyin combinations of two words. In the process of information hiding, the part of speech (POS) is used for hiding the number of keywords. Also, the redundancy of hidden tags in extraction process is eliminated by ensuring the uniqueness of each hidden tag in each stego-text. Meanwhile, the way of joint retrieval is used for hiding multi-keywords. Experimental results show that the proposed method has good performance in the hiding capacity, the success rate of hiding, the extraction accuracy and the time efficiency with appropriate hidden tags and large-scale of the big text data.